Faculty Members’ Perceptions and Expectations of the Quality of Administrative Academic (Journal Of Educational and Psychological Researches, 2024)
The study aims to determine faculty members' perceptions and expectations of the quality of administrative and academic services provided by heads of departments at the Jordanian universities and whether there are any significant differences based on faculty affiliation. Data was collected from a random sample of 215 faculty members (28% of the population) using a questionnaire with 26 items related to administrative and academic services. The results indicated there are no significant differences based on faculty affiliation in the perceptions and expectations of the department heads' performance. Faculty members' expectations were found to be very high, while the perceptions of the quality of administrative and academic services provided by heads of departments were moderate. Furthermore, there is a noticeable gap between perceptions and expectations of the quality of administrative and academic services. Based on these findings, it is recommended that the effectiveness of department heads be improved to meet the needs and expectations of faculty members. Additionally, department heads should be granted appropriate authority commensurate with their duties and roles to ensure high standards of quality in academic departments at Jordanian universities.